Clinical diagnosis of progressive supranuclear palsy: The movement disorder society criteria. Issue 6 (3rd May 2017) - Höglinger, Günter U.; Respondek, Gesine; Stamelou, Maria; Kurz, Carolin; Josephs, Keith A.; Lang, Anthony E.; Mollenhauer, Brit; Müller, Ulrich; Nilsson, Christer; Whitwell, Jennifer L.; Arzberger, Thomas; Englund, Elisabet; et al.
ABSTRACT: Background : PSP is a neuropathologically defined disease entity. Clinical diagnostic criteria, published in 1996 by the National Institute of Neurological Disorders and Stroke/Society for PSP, have excellent specificity, but their sensitivity is limited for variant PSP syndromes with presentations other than Richardson's syndrome. Objective : We aimed to provide an evidence‐ and consensus‐based revision of the clinical diagnostic criteria for PSP. Methods : We searched the PubMed, Cochrane, Medline, and PSYCInfo databases for articles published in English since 1996, using postmortem diagnosis or highly specific clinical criteria as the diagnostic standard. Second, we generated retrospective standardized clinical data from patients with autopsy‐confirmed PSP and control diseases. On this basis, diagnostic criteria were drafted, optimized in two modified Delphi evaluations, submitted to structured discussions with consensus procedures during a 2‐day meeting, and refined in three further Delphi rounds. Results : Defined clinical, imaging, laboratory, and genetic findings serve as mandatory basic features, mandatory exclusion criteria, or context‐dependent exclusion criteria. We identified four functional domains (ocular motor dysfunction, postural instability, akinesia, and cognitive dysfunction) as clinical predictors of PSP. Within each of these domains, we propose three clinical features that contribute different levels of diagnostic certainty. Specific combinations of these features define the diagnostic criteria, stratified by three degrees of diagnostic certainty (probable PSP, possible PSP, and suggestive of PSP). Clinical clues and imaging findings represent supportive features. Conclusions : Here, we present new criteria aimed to optimize early, sensitive, and specific clinical diagnosis of PSP on the basis of currently available evidence. © 2017 International Parkinson and Movement Disorder Society